RAG-Guardrails Integration for AI Content Control - Rakesh More (International Journal of Artificial Intelligence, 2025)
Generative AI is particularly Large Language Models (LLMs), has shown remarkable potential across domains such as healthcare, legal services, and finance. However, their adoption is hindered by two persistent challenges: hallucination, where models generate factually incorrect information and the risk of producing biased or unsafe content. This paper proposes a hybrid framework that integrates Retrieval-Augmented Generation (RAG) with NVIDIA NeMo Guardrails to address these concerns. RAG mitigates hallucinations by grounding model outputs in externally retrieved, trusted data sources, while NeMo Guardrails enforce domain-specific safety and compliance constraints through predefined behavioral policies. Empirical evaluations demonstrate that this combined approach reduces hallucinated content by 30–45% and improves safety and policy adherence across multiple enterprise use cases. The system exhibits strong potential for deployment in regulated, high-stakes environments. Future work will focus on enhancing real-time responsiveness and expanding multilingual and culturally adaptive capabilities. The proposed framework offers a scalable foundation for building trustworthy, domain-aligned generative AI solutions.